Evaluation of skill-oriented training on enhanced syndromic case management (ESCM) of reproductive tract infections / sexually transmitted infections (RTI/STIs) of care providers from three-tier health-care system of Gujarat - Rashmi Sharma; Shailesh Prajapati; Brijesh Patel; Pradeep Kumar (Wolters Kluwer Medknow Publications, 2016)
Background: Enhanced syndromic case management (ESCM) deals with reproductive tract and sexually transmitted infections. Capacity building of service providers not only boosts the program but also inputs from them improve the quality of services. Objectives: To (1) identify problem areas from providers' perspectives and the gaps in knowledge and application and (2) assess the gains (if any) through pre and post-training evaluation. Materials and Methods: A total of 121 participants (medical/para medical) from various medical colleges, district/sub-district hospitals/ community health centers, and urban dispensaries across Gujarat were trained at a teaching institute. Trainings were of 2-3 days duration involving different learning methodology. Pre- and post-training evaluation were done on a designed pro forma and data were entered in MS office Excel 2007. Gains in knowledge/skills if any were assessed by comparing pre-/post-evaluation responses and applying test of significance (x2 test). Observations: Out of total 121 participants, half (60) were doctors and the rest were paramedics [staff nurse (SN) and lab technicians (LT)]. Doctors revealed significant gain in basics of reproductive tract infections (RTI) and sexually transmitted infections (STI), syndrome identification, STI/HIV co-infection, and ESCM and less gain in asymptomatic STI/ complications, vulnerability, male reproductive organs, causes of vaginal/urethral discharge, STI complications, cervical cancer screening, and limitation of syndromic management. Gain was statistically significant in basics of RTI/STI amongst adolescent in paramedics; lab technicians showed significant gain in knowledge of laboratory-related areas. Conclusion: Assessment revealed (1) poor baseline knowledge and (2) gains following training sometimes significant and other times not significant even in core areas. Quality monitoring and contents/ methodologies modification are essential for robust trainings. Gains in skills could not be assessed through this evaluation.